Recollections of lectures delivered by Jerzy Brycki at the University of Physical Education in Krakow: “Chess as a form of rehabilitation of the blind” - Sobiecka, Joanna (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The paper presents the Author’s memories regarding the monograph lectures presented by the doyen of Polish chess for the blind - Jerzy Brycki, which were part of the Disability Sport curriculum. The lectures were delivered in the University of Physical Education in Krakow and their main theme was “Chess as a form of rehabilitation of the blind”. Prior to the lectures, the Author participated (as an observer) in chess trainings and tournaments which she recalls as extraordinary emotional experiences. First, thanks to the opportunity to observe the blind players who remained deeply focused in an absolutely quiet room. Second, due to the unique character of the competitions as the players used only their memory and imagination. These experiences had inspired the Author to invite the Royal Game enthusiast to meet the movement rehabilitation students. Each lecture delivered by the Master was both theoretical and practical. In the first part, Jerzy Brycki presented a brief history overview, the game rules when the blind plays against a sighted player, and the nature of learning chess. Using his own example, he emphasised the role of the game in psychical adaptation as well as intellectual, emotional and social development. The practical part included a blind chess match. Jerzy Brycki played using his memory whereas students used a Braille chess set. After the game, in order to explain the students’ failure, the Master always asked them to reconstruct the positions of pieces on the board. Then, as during a “bling game”, that is, a game played in memory, without the board - he began to replay the match. He instructed the captain how to move the pieces, one by one, the blacks and the whites, and commented the students’ moves. As a result, Jerzy and his wife were invited to share their playing and training experiences during the National Scientific and Methodic Conference titled: “Sport for persons with disabilities in different age groups”. During the 1st Scientific and Methodic Session Mr and Mrs Brycki delivered a presentation titled “Chess as a form of rehabilitation of the blind”, which was highly rated by the Conference Scientific Board.